New Insights into Molecular Mechanisms of Chronic Kidney Disease - Weronika Frąk; Joanna Kućmierz; Magdalena Szlagor; Ewelina Młynarska; Jacek Rysz; Beata Franczyk (Biomedicines, 2022)
Chronic kidney disease (CKD) is a major public health problem with a developing incidence and prevalence. As a consequence of the growing number of patients diagnosed with renal dysfunction leading to the development of CKD, it is particularly important to explain the mechanisms of its underlying causes. In our paper, we discuss the molecular mechanisms of the development and progression of CKD, focusing on oxidative stress, the role of the immune system, neutrophil gelatinase-associated lipocalin, and matrix metalloproteinases. Moreover, growing evidence shows the importance of the role of the gut–kidney axis in the maintenance of normal homeostasis and of the dysregulation of this axis in CKD. Further, we discuss the therapeutic potential and highlight the future research directions for the therapeutic targeting of CKD. However, additional investigation is crucial to improve our knowledge of CKD progression and, more importantly, accelerate basic research to improve our understanding of the mechanism of pathophysiology.